Resistance of Several Hibiscus cannabinus genotypes Against Meloidogyne incognita - Parnidi Parnidi; Lita Soetopo; Damanhuri Damanhuri; Marjani Marjani (The Indonesian Phytopathological Society (Perhimpunan Fitopatologi Indonesia), 2021)
Resistance of Several Hibiscus cannabinus genotypes Against Meloidogyne incognita Kenaf (Hibiscus cannabinus) is known as a source of natural fibers. Infection of Meloidogyne incognita (root-knot nematode) in kenaf plants causes stunting of plants, thereby reducing crop production. This study aimed to determine the resistance of seven kenaf genotypes against M. incognita. The experiment was conducted by infesting kenaf plants aged 15 days after planting (DAP) with M. incognita in a population of 40 juvenile nematodes 2 per 100 g of soil. The planting medium used was sandy soil with a composition of 55% sand, 36% dust, and 17% clay. The resistance variable consisted of root knot index and nematode reproduction factors. Analysis of salicylic acid, phenol, lignin and several plant growth variables were carried out at 75 DAP. Among the seven kenaf plant genotypes evaluated, there were 3 tolerant genotypes (KR4, KR15 and KR5) and 4 highly susceptible genotypes (KR1, KR6, Kin2, and DS028). Genotypes that had a tolerant response to M. incognita showed an increase in phenolic compounds, salicylic acid, and lignin in the roots compared to the control. The decrease in plant height, crown fresh weight, and root fresh weight varied due to M. incognita infection.